2015
DOI: 10.12659/msm.893792
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Intake and Pancreatic Cancer Risk: A Meta-Analysis of Observational Studies

Abstract: BackgroundSome epidemiological studies have suggested that vitamin E intake reduces the risk of pancreatic cancer; however, this conclusion has not been supported by all the published studies. We conducted a meta-analysis to assess the relationship between vitamin E intake and the risk of pancreatic cancer by combining the results from published articles.Material/MethodsWe searched the published studies that reported the relationship between vitamin E intake and pancreatic cancer risk using the PubMed, Web of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
(34 reference statements)
0
30
0
Order By: Relevance
“…conducted a meta-analysis to assess the relationship between dietary vitamin C and pancreatic cancer risk and found that a higher vitamin C intake was inversely correlated with pancreatic cancer risk7. Similarly, dietary vitamin E was found to be a protective factor against pancreatic cancer8. However, a recent pooled analysis suggested that higher levels of vitamin D might increase pancreatic cancer risk30.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…conducted a meta-analysis to assess the relationship between dietary vitamin C and pancreatic cancer risk and found that a higher vitamin C intake was inversely correlated with pancreatic cancer risk7. Similarly, dietary vitamin E was found to be a protective factor against pancreatic cancer8. However, a recent pooled analysis suggested that higher levels of vitamin D might increase pancreatic cancer risk30.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiologic studies have been published in an attempt to explore the relationship between nutrient intake and the risk of pancreatic cancer occurrence. Various vitamins including vitamin B6, vitamin C7 and vitamin E8 have been implicated in the risk of pancreatic cancer occurrence according to previous studies.…”
mentioning
confidence: 97%
“…Several epidemiological studies investigating the effects of AA against breast cancer link many inconsistent results, but, reports indicate that it can also reduce the risk of this type of cancer due to its antioxidant action for protection of DNA damage by neutralizing the free radicals and initiation of carcinogenesis [48].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have revealed that tobacco smoke (TS), the environment and diet are primary risk factors for BC, in addition to drinking water contaminants, including chlorinated byproducts and arsenic, the use of pioglitazone, obesity, hypertension and diabetes (2,6,7). A previous study reported that 23% of female and 50% of male BC cases have been attributed to TS (8).…”
Section: Introductionmentioning
confidence: 99%